Immune-checkpoint protein VISTA in allergic, autoimmune disease and transplant rejection - Zheng, Meijun; Zhang, Zongliang; Yu, Lingyu; Wang, Zeng; Dong, Yijun; Tong, Aiping; Yang, Hui (Frontiers in Immunology, 2023)
Negative checkpoint regulators (NCRs) reduce the T cell immune response against self-antigens and limit autoimmune disease development. V-domain Ig suppressor of T cell activation (VISTA), a novel immune checkpoint in the B7 family, has recently been identified as one of the NCRs. VISTA maintains T cell quiescence and peripheral tolerance. VISTA targeting has shown promising results in treating immune-related diseases, including cancer and autoimmune disease. In this review, we summarize and discuss the immunomodulatory role of VISTA, its therapeutic potential in allergic, autoimmune disease, and transplant rejection, as well as the current therapeutic antibodies, to present a new method for regulating immune responses and achieving durable tolerance for the treatment of autoimmune disease and transplantation.